Case for God - "Armstrong, Karen" (London, 2009)
The enormous popularity of books by Richard Dawkins, Christopher Hitchens, Sam Harris and others shows that despite the religious revival that is under way in many parts of the world, there is widespread confusion about the nature of religious truth. The militant atheism we are witnessing at present is a historical phenomenon, a product of modernity. his groundbreaking book will examine this Western recoil from religion in an historical context, showing how our rational, scientific culture has distorted the notion of religious faith. It will explore the way people were religious in the past, investigate the original significance of religious dogmas and creeds, show how they were interpreted by later generations and reveal how they have been misunderstood in our contemporary world. We will explore fundamental notions, such as God , belief , scripture and truth , showing how their meaning changed radically during the 18th century European Enlightenment, and will discuss the relationship between science and religion- are the two incompatible or complementary? How does religious truth differ from the truths of science or art? And finally, it will look at the future of religion.
Keywords: God